EFEKTIVITAS PELAKSANAAN PROGRAM PEMBANGUNAN INFRASTRUKTUR PERDESAAN DI DESA KAYUUWI 1 KECAMATAN KAWANGKOAN BARAT KABUPATEN MINAHASA - WATUNG, JESIKA; ROMPAS, WELSON; TAMPONGANGOY, DEYSI (Sam Ratulangi University, 2021)
Limitation of infrastructure, such as providing access to economic centers, access to plantations and theavailability of clean water, became the obstacle of the rural developing. This research uses a qualitativeapproach. Data obtained from interviews, observations, and documentation. The data obtained were thenanalyzed use data reduction techniques, data models, and verification. The focus of this study refer to fiveindicators of the effectiveness of implementing the rural infrastructure development program, namely theright policy, the right implementation, the right target, the right environment, and the right process. Righton policy, government policies regarding existing problems such as construction of production roads,provide the clean water and productive businesses can be resolved. Appropriate implementation, theimplementation of rural infrastructure development was carried out in stages or gradually. Right ontarget, the target of rural infrastructure development is to realize increased access for the poor and in thisachievement the government has designated Kayuuwi 1 as the target group by involving the community.Environmentally appropriate, assessment by institutions involved in implementation and involve thecommunity as a group that related institutions and the community alike positively assess the PPIPprogram implemented in Kayuuwi 1. Appropriate process, the process starts from planning,implementation, and supervision, to decision making. The existing process is working and PPIP inKayuuwi 1, West Kawangkoan is proceeding according to the existing process.Keyword : programs effectiveness, infrastructure, rural development